Inside Back Cover: Thermochromic Magnetic Ionic Liquids from Cationic Nickel(II) Complexes Exhibiting Intramolecular Coordination Equilibrium (Chem. Eur. J. 4/2017). Issue 4 (5th December 2016) - Lan, Xue; Mochida, Tomoyuki; Funasako, Yusuke; Takahashi, Kazuyuki; Sakurai, Takahiro; Ohta, Hitoshi
Abstract : Thermochromic magnetic ionic liquids that contain cationic metal–chelate complexes have been developed. These liquids exhibit color changes between red at high temperatures and orange, blue, or blue green at lower temperatures depending on the cation. This phenomenon is based on temperature‐dependent coordination equilibrium. More information can be found in the Full Paper by T. Mochida et al. onpage 823 ff.